2010
DOI: 10.1177/1043454209357923
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ and Parents’ Experiences of Managing the Psychosocial Impact of Appearance Change During Cancer Treatment

Abstract: Using combined qualitative data from multiple case study interviews and an online survey, this study explored the impact of appearance change on 22 adolescents receiving cancer treatment aged 13 to 18 years and six of their parents. Data were analyzed using template analysis. Appearance changes were a major concern. Adolescents typically struggled to adapt to new experiences and concerns related to this highly sensitive issue. Many felt anxious and self-conscious and were reluctant to reveal appearance changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 20 publications
8
101
0
8
Order By: Relevance
“…They were concerned that some people did not know how to interact with their child; there were several stories about strangers staring and asking invasive and personal questions. Parental support of young people with an altered appearance has previously been discussed by researchers including Williamson et al (2010) who found that parents of adolescents who seemed to be coping well with an altered appearance were those who felt confident and able to support their child's integration. Williamson et al also noted that parents often wanted advice on helping their child to feel positive about their appearance and manage their concerns or negative reactions from others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were concerned that some people did not know how to interact with their child; there were several stories about strangers staring and asking invasive and personal questions. Parental support of young people with an altered appearance has previously been discussed by researchers including Williamson et al (2010) who found that parents of adolescents who seemed to be coping well with an altered appearance were those who felt confident and able to support their child's integration. Williamson et al also noted that parents often wanted advice on helping their child to feel positive about their appearance and manage their concerns or negative reactions from others.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has pointed to differences in young people's and their parents' perceptions of living with NF1; parents have been found to be more pessimistic on measures such as social inclusion (Sebold et al 2004;Wolkenstein et al 2008), and whilst parents play a crucial role in supporting young people to develop the skills needed to positively manage chronic health conditions as they transition from childhood to adulthood (Michaud et al 2004;WHO 2013), and play a central role in young people's adjustment to visible difference (Prior and O'Dell 2009;Williamson et al 2010), there has been a lack of research specifically into their experiences of caring for a child or young person with NF1 and their own support needs. We therefore set out to address this gap in the literature, in order to inform the provision of support and care for young people and their parents.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52][53][54][55] Being able to participate in physical activity is viewed as important in both the CF and asthma populations. 56 What may be unique in children and adolescents with CF is how their susceptibility to infections (including cross-infection necessitating segregation 32,57,58 ) limits their lifestyle, reduces their capacity to participate in physical activity, and perpetuates anxiety, isolation, and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Body image and perceived physical appearance have been previously identified as areas of concern in children with cancer, specifically in adolescents. 93,94 Our study identified similar patterns of lower perceived physical appearance scores in adolescents and females. It also identifies children with melanoma, mainly composed of adolescents, as a group that may require further intervention and research into the perceived body image and physical appearance during and following treatment.…”
Section: Aimsupporting
confidence: 66%